Laparoscopic robotic-assisted "keel" bladder neck construction. Issue 6 (December 2020) - Minoli, D.G.; De Marco, E.A.; Gnech, M.; Rocco, B.; Manzoni, G.; Berrettini, A.
Summary: Introduction: Robotic technology has gained popularity allowing performance of several complex and difficult reconstructive procedures. This video demonstrates the advantages of the robotic approach for a "keel" bladder neck construction in an obese patient. Material and methods: A 13 year-old-girl (BMI = 28) already treated elsewhere for a uro-genital sinus (Total Urogenital Mobilization) has been evaluated for disturbing persistent total urinary incontinence. Cisto-colposcopy revealed an extremely short and tortuous urethra. Bladder neck was wide open and incompetent. Video-Urodynamic evaluation showed a bladder with a capacity of 280 mL with low voiding pressures (14–16 cmH20) and continuous urinary leakage. MAG3 scan confirmed normal renal function. Thus, the girl underwent a laparoscopic robotic-assisted "keel" bladder neck construction. Results: The patient was discharged on 5th post-operative day without complications. After 4 years she is voiding spontaneously (300 cc) without post-void residuals. She has presented a persistent mild stress incontinence successfully treated with subsequent endoscopic bulking agent injection. Conclusions: Robotic access to the bladder neck region is an excellent option with ideal anatomical exposure compared to conventional open surgery, especially in obese patients. The "keel" procedure allows to reconfigure and tubularize a wide and incompetent bladder neck creating a continent funnel without the absolute need of concomitant ureteric reimplantation.